Antimicrobial and antibiofilm activities of the methanol extracts of rosa damascena against s. aureus / Indah Mohd Amin … [et al.] - Mohd Amin, Indah; Mohamad Zain, Nurhayati; Ahmad, Vivi Noryati; Mat Daud, Dzulfakhrul Najwan; Abdullah Sani, Nabilah (2019)
The aims of this study are to investigate antibacterial and antibiofilm activity of Rosa damascena (R.damascena) flower extract against Staphylococcus aureus (S. aureus). Method: The antibacterial activity was assessed with minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC). The potential of R.damascena flower extract as an antibiofilm agent was evaluated using biofilm inhibition assay and biofilm eradication assay. Chlorhexidine (CHX) 0.12% was used as a positive control. The experiment was performed in triplicate and repeated four times independently. All the data obtained were analysed using SPSS version 23. A Kruskal-Wallis test followed by post-hoc Mann-Whitney U test and level of significance was set at P < 0.05. Results: From this study, R.damascena extract shows antibacterial activity with MIC 50 mg/ml and MBC 100 mg/ml. Treatment with 0.5 MIC of extract inhibited 43.2% of biofilm formation. The biofilm eradication assay shows that 60.9% (p<0.001) of biofilm was eradicated by the extract upon 5 minutes treatment and 50.65% by 0.12% CHX. Conclusion: The result of this in-vitro study suggests a possible utilisation of R.damascena flower extract in treating S. aureus biofilm-associated infection in the oral environment.